2017
DOI: 10.1128/aac.01542-16
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Exposure to Increasing Micafungin Concentrations Easily Promotes Echinocandin Resistance in Candida glabrata Isolates

Abstract: We assessed the in vitro susceptibility of five echinocandin-susceptible Candida glabrata isolates after exposure to micafungin. The direct exposure to plates at different micafungin concentrations resulted in the inhibition of growth at 0.062 g/ml. The progressive exposure was performed on plates using 0.031 g/ml of micafungin and sequential propagation on plates containing the next 2-fold concentration; the MICs of micafungin and anidulafungin increased sequentially, and all the isolates became echinocandin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 15 publications
1
24
1
Order By: Relevance
“…The different HS1 mutations did not result in different MIC values. This contrasts with previous studies that suggested that C. glabrata isolates harboring the D666Y mutation in FKS2 show weak resistance, while the S663P mutation confers strong resistance (22,23). Additionally, we did not find any mutations in HS2 and like in previous studies, most of the mutations influencing C. glabrata echinocandin susceptibility were located in HS1 of either FKS gene (6,8,24).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The different HS1 mutations did not result in different MIC values. This contrasts with previous studies that suggested that C. glabrata isolates harboring the D666Y mutation in FKS2 show weak resistance, while the S663P mutation confers strong resistance (22,23). Additionally, we did not find any mutations in HS2 and like in previous studies, most of the mutations influencing C. glabrata echinocandin susceptibility were located in HS1 of either FKS gene (6,8,24).…”
Section: Discussioncontrasting
confidence: 99%
“…Fourteen resistant isolates were detected by the MBT ASTRA that had no HS mutations in FKS genes. In routine clinical practice, in which usually no gene sequencing is performed, it has obviously not been noticed that there are C. glabrata isolates with elevated MIC values for echinocandins without mutations in the FKS1 and/or FKS2 gene (22,28). However, there are some possible explanations for this observation, which is also known as adaptive response (29,30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The emergence of echinocandin resistance in Denmark follows a significant increase in echinocandin consumption from 2004 to 2015. These observations suggest that longer-term administration of echinocandin, including its empirical use, should be minimized if possible (63,64).…”
Section: Discussionmentioning
confidence: 96%
“…Parental isolates were phenotypically echinocandin susceptible, and isogenic ones were phenotypically echinocandin resistant. Pairs 1 to 8 came from a previous study and involved susceptible isolates from blood samples exposed in vitro to either micafungin or anidulafungin and the corresponding resistant ones generated (27,28). Pairs 9 and 10 originated in two patients with candidemia who developed concomitant echinocandin-resistant endocarditis.…”
Section: Discussionmentioning
confidence: 99%